2011
DOI: 10.2147/ahmt.s26560
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and risk and protective behaviors: a global health perspective

Abstract: Social capital and health research has emerged as a focus of contemporary behavioral epidemiology, while intervention research is seeking more effective measures to increase health protective behaviors and decrease health-risk behaviors. In this review we explored current literature on social capital and health outcomes at the micro-, mesa-, and macro-levels with a particular emphasis on research that incorporates a social capital framework, and adolescent and young adult engagement in risk behaviors. These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…Derived from economics and finance, social capital theory has successfully guided numerous researchers in advancing our understanding of the impact of social factors on health in both developed and developing countries across the globe (Murayama et al 2012; Kaljee and Chen 2011). Converging evidence from diverse sources strongly suggests the existence of a positive relationship between social capital and health at the individual (Berkman et al 2000; Chen et al 2009a, 2011; Nieminen et al 2010; Norstrand and Xu 2012; Poortinga 2006), community (Bartkowski and Xu 2007; Lochner et al 2003; Miller et al 2006; Poortinga 2006), national and global levels (Kawachi et al 1997; Kennelly et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Derived from economics and finance, social capital theory has successfully guided numerous researchers in advancing our understanding of the impact of social factors on health in both developed and developing countries across the globe (Murayama et al 2012; Kaljee and Chen 2011). Converging evidence from diverse sources strongly suggests the existence of a positive relationship between social capital and health at the individual (Berkman et al 2000; Chen et al 2009a, 2011; Nieminen et al 2010; Norstrand and Xu 2012; Poortinga 2006), community (Bartkowski and Xu 2007; Lochner et al 2003; Miller et al 2006; Poortinga 2006), national and global levels (Kawachi et al 1997; Kennelly et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While education has a protective effect on health (55), some of this protective effect may be due to income (56). We showed that in some countries, education and income have independent effects, and that in some other countries education, but not income, has independent effects.…”
Section: Discussionmentioning
confidence: 70%
“…The polarity of views and acts of aggression against immigrants or even all foreigners cause anxiety, identity and even personality disorders [31][32][33][34][35][36][37][38]. This obstructs social and economic development [39].…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to understand what the real possibilities are of the peaceful coexistence of Muslims and Christians, what the content is of the most common and deepest ethnic and cultural prejudices [33][34][35][36][37][38][39][40][41][42][43]. We have to understand why the Christian message is not a guideline of conduct and even the recommendations of the sovereignty of the church are rejected [44].…”
Section: Resultsmentioning
confidence: 99%